Effects of Globalization on Labor's Share in National Income - Guscina, Anastasia (IMF Working Papers; Working Paper ;, 2006)
The past two decades have seen a decline in labor's share of national income in several industrial countries. This paper analyzes the role of three factors in explaining movements in labor's share--factor-biased technological progress, openness to trade, and changes in employment protection--using a panel of 18 industrial countries over 1960-2000. Since most studies suggest that globalization and rapid technological progress (associated with accelerated information technology development) began in the mid-1980s, the sample is split in 1985 into preglobalization/pre-IT revolution and postglobalization/post-IT revolution eras. The results suggest that the decline in labor's share during the past few decades in the OECD member countries may have been largely an equilibrium, rather than a cyclical, phenomenon, as the distribution of national income between labor and capital adjusted to capital-augmenting technological progress and a more globalized world economy.